A non-destructive virtual dissection by micro-CT reveals diagnostic characters in the type specimen of Caloptilia stigmatella (Lepidoptera: Gracillariidae) - Robinson, Jeanne; Gibson, Jeremy; Arévalo-Maldonado, Helber Adrián; de Prins, Jurate; Windmill, James (Zootaxa, 2018)
Nearly a century ago, wing venation was introduced in gracillariid taxonomy as a means to diagnose closely related genera and species groups. Recent advances in non-destructive virtual micro-dissections suggest promising approaches with which to revisit the relevance of wing venation characters on historic primary type specimens. Many unique type specimens in Gracillariidae and other microlepidoptera groups preserved in museum collections are in poor condition, and over the course of history have suffered loss or damage to their abdomens. Consequently, genitalia morphology is not available for diagnoses and comparisons. In this paper we emphasize the need to include the type species and type specimens into the broader context of taxonomic studies on micro-moths in general and the family Gracillariidae in particular. The genus Caloptilia has a world-wide distribution and has been the subject of research for more than 200 years, yet the generic boundaries and groupings within the genus are still unresolved due to the lack of a reliable set of taxonomic characters obtained from the primary types. We describe a method of virtual descaling of the fore- and hindwings using the unset micro-moth type specimen of Caloptilia stigmatella Fabricius, 1781, in order to demonstrate that the study of historic and fragile type specimens and diagnoses of their internal morphological characters becomes possible by applying new and non-destructive technology.